EKSPERIMENTASI MODEL PEMBELAJARAN TTW DAN NHT PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Rahmawati, Nurina Kurniasari; Budiyono, Budiyono; Sari S, Dewi Retno (Jurnal Pembelajaran Matematika, 2014)
Abstract: The aim of the research was to find out the effect of learning models on mathematics achievement viewed from the student mathematics communications ability. The learning model compared were TTW (Think Talk Write), NHT (Numbered Head Together) and conventional. The type of the research was a quasi-experimental by 3 12Ãâ"> 3 factorial design. The population was the eight grade student of junior high school in Magelang regency on academic year 2013/2014. The sampling tecnique was stratified cluster random sampling. The size of the sampel was 298 students consisted of 100 students in the first experimental group, 99 students in second experimental group and 99 students in control group. The instruments used were mathematics achievement test and mathematics communication ability test. The data was analyzed using unbalanced two-way analysis of variance. The conclusions of the research were as follows. (1) TTW learning model gives better mathematics achievement than NHT and conventional learning model, and NHT learning model gives better mathematics achievement than conventional learning model. (2) The students with high mathematics communication ability have better mathematics achievement than the students with middle or low mathematics communication ability, the students with middle mathematics communication ability have better mathematics achievement than the students with low mathematics communication ability, (3) a. In the students with high and middle mathematics communication ability, TTW, Â NHT and conventional learning model give the same mathematics achievement, Â b. In the students with low mathematics communication ability, TTW and NHT learning model give the same mathematics achievement, but give better mathematics achievement than conventional learning model, also NHT and conventional learning model give the same mathematics achievement, (4) a. In the TTW and NHT learning model, students with high, middle and low mathematics communication ability have the same mathematics achievement, b. In the conventional learning model, students with high and middle mathematics communication ability have the same mathematics achievement, but have better mathematics achievement than students with low mathematics communication ability, and students with middle and low mathematics communication ability have the same mathematics achievement.Keywords: TTW, NHT, mathematics communication ability, mathematics achievement